Excessive Smartphone Use Is Associated With Health Problems in Adolescents and Young Adults - Wacks, Yehuda; Weinstein, Aviv M. (Frontiers in Psychiatry, 2021)
Background and aims: This present paper will review the existing evidence on the effects of excessive smartphone use on physical and mental health. Results: Comorbidity with depression, anxiety, OCD, ADHD and alcohol use disorder. Excessive smartphone use is associated with difficulties in cognitive-emotion regulation, impulsivity, impaired cognitive function, addiction to social networking, shyness and low self-esteem. Medical problems include sleep problems, reduced physical fitness, unhealthy eating habits, pain and migraines, reduced cognitive control and changes in the brain's gray matter volume. In conclusion, excessive smartphone use is associated with psychiatric, cognitive, emotional, medical and brain changes that should be considered by health and education professionals.